Review: Visual Performance Assessments for Sport. Issue 7 (July 2021) - Erickson, Graham B.
Abstract : SIGNIFICANCE: Eye care professionals seek to provide effective vision care for a variety of patient needs, including performance in sports and recreational pursuits. This review provides an analysis of common visual performance assessments, including summaries of recent clinical research from a diverse array of professional literature. Vision is recognized as an important element of sports performance. Elite athletes frequently demonstrate exceptional abilities to see and respond effectively in sports competition. Which visual factors are important and how to most effectively assess visual performance are the sources of much debate. This topical review presents an evidence-based review of the common visual performance factors assessed in athletes, beginning with guidance for conducting a visual task analysis for the variety of sports that athlete patients may compete in. An information processing model is used to provide a framework for understanding the contributions of the many visual performance factors used during sports.